THE USE OF GRAPH MODELS IN THE TASK OF DIAGNOSING FAULTS IN THE CIRCLES OF CONTROL LOCOMOTIVE CHS7 - Petrovych, L. V.; Holik, S. M. (Science and Transport Progress, 2005)
A modernization option of onboard test units of the electric locomotive ChS7 on the basis of use of control electric circuits flow-charts for calculation of the minimal number and location of the control points has been proposed in the article.